1999
DOI: 10.1038/sj.ijo.0800906
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance programmes after weight reduction — how useful are they?

Abstract: Maintenance programmes lasting one or two years or even longer are generally recommended to improve long-term outcome after weight reduction. They may not be practical for several reasons: it is not known whether they really improve long term outcome or only delay relapse; they may lessen patients' motivation to take full responsibility for their life-style changes; and they need extra resources. Some series on treatment of obesity and experience with successful maintainers suggest that satisfactory long-term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 11 publications
0
9
0
1
Order By: Relevance
“…Analysing individual moderators of weight control is especially important when we consider the large and increasing number of treatment modalities available, which vary in caloric restriction, structure, type and level of support, philosophy and conceptual model and in several other ways (33). Low‐carbohydrate diets (19), meal replacement plans (164), exercise‐only (20) and non‐dieting approaches (165) are available, as are self‐help (166), Internet‐ (167) and doctor‐delivered modalities (168,169), individual, psychologically intense programmes (170), short‐term interventions (171), long‐term care (172) and various combinations of the above [e.g. (173)].…”
Section: Resultsmentioning
confidence: 99%
“…Analysing individual moderators of weight control is especially important when we consider the large and increasing number of treatment modalities available, which vary in caloric restriction, structure, type and level of support, philosophy and conceptual model and in several other ways (33). Low‐carbohydrate diets (19), meal replacement plans (164), exercise‐only (20) and non‐dieting approaches (165) are available, as are self‐help (166), Internet‐ (167) and doctor‐delivered modalities (168,169), individual, psychologically intense programmes (170), short‐term interventions (171), long‐term care (172) and various combinations of the above [e.g. (173)].…”
Section: Resultsmentioning
confidence: 99%
“…Allowing the patient to choose the preferred method to make lifestyle changes may be one approach to long-term dietary maintenance. 28 In this study, participants who perceived that they were maintaining the diet possessed the confidence and skills necessary to adapt to new routines and not slip back to old habits completely. Maintenance may actually be a state of constant change, where adaptability and flexibility with physical, social, and environmental conditions are critical to prolonging the desired change.…”
Section: Relationships With Family Friends and Health Care Providersmentioning
confidence: 91%
“…In studies longer than a year, some weight regain is observed even with continued intervention [121,122]. More importantly, when the beneficial drug or lifestyle intervention is discontinued, patients regain their lost weight quickly [60,123] and often return to their pre-intervention weight over the next 1 --5 years [124][125][126][127]. Clinicians, however, should base their decisions regarding long-term continuation of pharmacotherapy for obesity not just on weight-loss efficacy, but also on improvements in comorbidities, quality of life and, more importantly, on tolerability and safety of the treatment.…”
Section: Issues In Using Antiobesity Drugs In Clinical Practicementioning
confidence: 99%